DRAMATURGY OF MIROSLAV IRCHAN AND YAROSLAV GALAN: GENRE-STYLISH DOMINANTS OF 20-30-H YEARS ХХ OF ITEM - Chorob, S. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The genre-stylish dominants of west Ukrainian dramaturgy of 20-30th years ХХ of age are explored; artistic achievements and failings are certain through their prism in creation till recently ideological canon writers.